The strange fate of the English "Arnalte y Lucenda" by Diego de San Pedro - Chamosa, José Luis (SEDERI: yearbook of the Spanish and Portuguese Society for English Renaissance Studies, 1992)
Quite by chance, when looking op a reference in the British Library Catalogue (the one in the Main Reading Room) last summer on behalf of a colleague of mine in the Spanish Departament, Y came across the name of Diego de San Pedro...